Digital Promotion Platforms And Cloud Spreadsheets Determine Construction Vendor Business Operations: Platform Promosi Digital Dan Lembar Kerja Awan Menentukan Operasional Bisnis Vendor Konstruksi - Bima Panduni Rahmat; Istian Kriya Almanfaluti (International Consortium of Education and Culture Research Studies, 2024)
General Background The rapid evolution of information technology fundamentally transforms modern commercial activities and online marketing strategies. Specific Background Infrastructure service providers like PT Sixma Mega Utama require optimized internet presence and accurate administrative systems to secure client trust and manage field logistics. Knowledge Gap Manual material recording triggers severe inventory inaccuracies and financial risks, while the absence of professional online profiles severely restricts market visibility and client acquisition. Aims This project develops a comprehensive company profile website, establishes an active social media account, and creates a transparent material monitoring system. Results Qualitative observation confirms the successful deployment of a Google Sites profile providing accessible corporate information and an Instagram account visualizing project portfolios. Furthermore, replacing manual logs with a multi-access online workbook establishes real-time, transparent logistics tracking for all field supervisors. Novelty This intervention uniquely integrates external visual marketing mechanisms with internal internet-based inventory administration to simultaneously resolve market visibility limitations and internal data bottlenecks. Implications Infrastructure enterprises must adopt transparent administrative tools and active online portfolios to secure market competitiveness and prevent financial losses from inventory mismanagement. Highlights: Social media portfolios successfully display service capabilities to potential market clients. Real-time material monitoring eliminates manual recording inaccuracies and inventory losses. Dedicated profile websites establish professional credibility and facilitate external communication. Keywords: Social Media Marketing, Inventory Management, Company Profile, Logistics Administration, Online Visibility